Re-reading the prologue of Sóngoro cosongo—Guillén as a poet of interconnectedness and mestizaje. - Novieto, Setor Donne (Revista Cedotic, 2025)
Abstract Critics have read Nicolás Guillén’s prologue to his second collection of poetry—Sóngoro cosongo—as a reflection of the poet’s inclination and attitude towards the issue of mixing of races (mestizaje) in Cuba in the late 1920s. This article considers the prologue to Guillén’s second collection of poems and other evidence from three essays he wrote earlier as an indication of Guillén’s poetry at the time, going beyond the quest of mestizaje, to seeking interconnectivity of races in Cuba. I argue that in the prologue, Guillén is working through the issue of how to articulate the way in which both Blacks and Whites can complement and complete each other in building the nation of Cuba in the late 1920s and beyond. Hence, Guillén is projecting the potential of him going beyond the poet of mestizaje, to being a poet of interconnectedness without being oblivious of the challenges at the time that will hinder this effort.